Pelatihan Desain Kemasan sebagai Upaya Meningkatkan Fungsi Komunikasi Pemasaran Produk Kopi Dadaman - Fadhilah Fadhilah; Diqbal Satyanegara; Widya Nur Bhakti Pertiwi (Universitas Majalengka, 2023)
Packaging is an important factor in improving the marketing communications function. Where marketing communications is an effort to promote products so they can compete. This service training aims to improve participants' skills, namely owners of Dadaman Coffee, in creating packaging and content designs using the Canva application. Apart from that, the results of this service are also in the form of printed packaging grants for Dadaman Coffee. The method of implementing community service activities is carried out in several stages: preparation, activity implementation, and evaluation. The service method in this service program is carried out by means of training and accompaniment. The training provided is in the form of material, tutorials and practice in the form of small group discussions accompanied by facilitators in each group. By holding this service activity, it is hoped that Dadaman Coffee products can improve the marketing communication function of their products, attract consumer attention and increase sales. With a continued commitment to effective packaging design, local brands can continue to thrive and succeed in a competitive advantage.